2023
DOI: 10.3390/nu15071681
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Rural Household Food Insecurity under the Taliban Regime

Abstract: Despite the severity of food insecurity in Afghanistan, little is known about the factors contributing to household food insecurity (HFI) under the Taliban regime. Therefore, this paper investigated the social determinants of severe HFI in rural areas of Afghanistan. We used the fifth-round survey of 6019 rural households from 25 provinces, collected between July and August 2022 by the Food and Agriculture Organization. We used binary logistic regression to examine the association between household characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…While the UN World Food Programme reported that 93% of Afghan households were Fig. 3 The difference of mean score of the QOL domains before and after Taliban's takeover food insecure in 2022 (a 13% increase compared to before the Taliban's governance) [34], the present study shows that the Taliban's takeover has led to a 40% increase in food insecurity among Afghan families. Some studies reported the negative effect of conflict on food security status previously [35].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…While the UN World Food Programme reported that 93% of Afghan households were Fig. 3 The difference of mean score of the QOL domains before and after Taliban's takeover food insecure in 2022 (a 13% increase compared to before the Taliban's governance) [34], the present study shows that the Taliban's takeover has led to a 40% increase in food insecurity among Afghan families. Some studies reported the negative effect of conflict on food security status previously [35].…”
Section: Discussioncontrasting
confidence: 45%
“…One year after the Taliban’s return to power in Afghanistan, the deplorable situation of Afghans is worsening. The economic situation is dire, the rate of malnutrition is increasing, the rights of women are under threat, and the health care system is collapsing [ 1 ]. The Taliban leadership has created conditions that have resulted in many Afghans being compelled to provide for their basic needs through unacceptable methods, such as selling their children, selling their kidneys, and giving sleeping medicine to children to consume less food [ 2 ].…”
Section: Introductionmentioning
confidence: 99%